Expansion of Parties Entitled to Receive Safekeeping of Compensation for Losses in Land Acquisition - Ketut Krisna Hari Bagaskara P.; I Wayan Parsa (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2024)
This study examines the expansion of those entitled to the safekeeping of compensation under Article 89 paragraph (3) of PP (Government Regulation) on Land Acquisition and its effects. Land acquisition is based on the state's right to control and the government's provision of land for compensation. The district court can serve as a repository for compensation funds, allowing for their secure management and distribution. As a result of the amendment included in Article 89 paragraph (3) PP on Land Acquisition, compensation is also granted to unidentified persons, which can be understood as land parcels whose owners are unidentified. This study takes a statutory and philosophical approach to normative juridical research. Based on the findings of this study, it is clear that the amendment to PP on Land Acquisition Article 89 paragraph (3) is to include land parcels for which the rightful owners cannot be located. The planned expansion is counter to Article 33, paragraph (3) of the 1945 Constitution of the Republic of Indonesia, together with UUPA (Basic Agrarian Law) and Land Acquisition Law, which establishes the state's power to control. Furthermore, from the perspective of its development, it shows that the government cannot expand the PP on Land Acquisition provisions outside the Land Acquisition Law. Since those three values—justice, certainty, and benefit—were left out of the law's formulation, the expansion in Article 89(3) of PP on Land Acquisition did not serve the goal of lawmaking.